2015
DOI: 10.2485/jhtb.24.181
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Oral Lichen Planus of Japanese Patients

Abstract: Oral lichen planus (OLP) can undergo malignant transformation and become squamous cell carcinoma (SCC). Oral infection with human papillomavirus (HPV) is associated with a significant risk of developing oral cancer. Although HPV DNA is detected more often in OLP tissue than in normal oral mucosa, there is as yet no firm evidence that HPV is a causative factor of malignant transformation in OLP. The objective of the present investigation was to assess HPV-genotype distribution in OLPs of Japanese patients and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…As early as 1987, the correlation between HPV and OLP was reported (11), but many studies were conducted after presenting different prevalence rates of HPV in this lesion. In this field, the findings of the present study, indicating the presence of 25% of HPV DNA, might be comparable to the results of some other studies (15)(16)(17)(18)(19)(20)(21)(22), which reported an HPV incidence rate of 15.4% to 42.6% for OLP and 0% to 7% for normal mucosa samples. However, lower incidence rates of 0.02% and 0.32% were also reported by Arirachakaran et al (35) and Szarka et al (36), respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As early as 1987, the correlation between HPV and OLP was reported (11), but many studies were conducted after presenting different prevalence rates of HPV in this lesion. In this field, the findings of the present study, indicating the presence of 25% of HPV DNA, might be comparable to the results of some other studies (15)(16)(17)(18)(19)(20)(21)(22), which reported an HPV incidence rate of 15.4% to 42.6% for OLP and 0% to 7% for normal mucosa samples. However, lower incidence rates of 0.02% and 0.32% were also reported by Arirachakaran et al (35) and Szarka et al (36), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…However, comparing the given subtypes, our findings would be comparable to studies conducted by O. flatharta et al (15) and Campisi et al (16), with a report of the most frequent subtypes, i.e., HPV-16 and HPV-33. However, in studies carried out by Kato et al (17) and Vasper et al (18), in addition to subtypes 16 and 33, other subtypes, including subtypes 31 and 18, were detected. Furthermore, Jontell et al (19) showed the presence of HPV-6 and HPV-16 in the erosive form of OLP; Sahebjamiee et al (20) detected subtypes of HPV-16 and HPV-18, and Siribang-on (22) reported that the most frequent subtypes were 16, 18, and 33.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 13 ] In a 10-year follow-up, the risk of oncogenesis of OLP ranges from 1.2% to 3.2%. [ 14 ] In contrast, Ma et al . [ 1 ] stated that the malignant transformation rate of OLP was 0–6.25%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that oral infection with HPV is associated with a significant risk of developing oropharyngeal cancer (OPSCC) 14,15) . There is also a potentially important causal association between HPV, OSCC and oral potentially malignant disorders (OPMD), as reported in a systematic review 8) .…”
Section: Discussionmentioning
confidence: 99%